BETA BLOCKERS: AN IMPORTANT THERAPEUTIC MODALITY FOR HYPERTENSIVE DIABETICS - Rehan, N.; Nasir, Khurram (Journal of Ayub Medical College Abbottabad, 2002)
Diabetes mellitus and hypertension are amongst the most common non-communicable diseases in Pakistan effecting nearly 2.7 and 10.8 million individuals respectively1. Both diseases are risk factors for cardiovascular disease and death2. The prevalence of hypertension is double among diabetics as compared to non-diabetics in the western world3. Similar findings have also been reported from Pakistan4. The risk of Cardio-vascular death in a hypertensive diabetic is twice that of a non-diabetic hypertensive and four times that of a non-diabetic without hypertension5. However it is distressing to know that a very low percentage of the Pakistani population is aware as well as treated for these conditions1. Beta-blockers (Î²-blockers) are well established in the treatment of coronary heart disease and hypertension6. However until recently they were considered relatively contraindicated among diabetic patient7-10. A recent meta-analysis by Psaty et al11, which was based on the results of 18 Randomized Controlled Clinical Trials with 50,000 patients, indicated that low dose thiazides (diuretics) and Î²-blockers are more effective as compared to other agents in reducing total mortality, cardiovascular mortality, stroke and myocardial infarction in individuals with hypertension. The results of this meta-analysis make Î²-blockers potentially a drug of choice among diabetic individuals with hypertension. Prospective studies have, however, indicated an increased risk of mortality in diabetic patients treated with diuretics12,13. As a result of these findings, the use of diuretics as the first line treatment for hypertension in diabetes mellitus has not been recommended14. This commentary aims to critically assess the common misconceptions held regarding the use of Î²-blockers among diabetic hypertensive patients and to explore the recent literature on use of Î²-blockers among hypertensive diabetic patients.